2020
DOI: 10.1007/s40858-020-00397-y
|View full text |Cite
|
Sign up to set email alerts
|

Variation in xylem characteristics of botanical races of Persea americana and their potential influence on susceptibility to the pathogen Raffaelea lauricola

Abstract: Avocado (Persea americana), an important fruit crop, is under threat from an invasive disease, laurel wilt. The pathogen, Raffaelea lauricola, spreads rapidly in the xylem of infected trees and causes a lethal vascular wilt. A previous study showed that variation in susceptibility to the disease exists among different races of avocado, with the West Indian race being most susceptible. To help elucidate potential explanations for differences in susceptibility, xylem characteristics were examined for fourteen av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…As several previous studies suggest, the survival of infected trees appears to be connected with the size of the vessels [ 45 , 46 , 47 ]. An assessment of constitutive traits, such as vessel characteristics before or at the time of infection, is needed and should be supplemented with the study of induced responses in cambial activity and the production of new vessels that were differentiated under specific stimuli.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…As several previous studies suggest, the survival of infected trees appears to be connected with the size of the vessels [ 45 , 46 , 47 ]. An assessment of constitutive traits, such as vessel characteristics before or at the time of infection, is needed and should be supplemented with the study of induced responses in cambial activity and the production of new vessels that were differentiated under specific stimuli.…”
Section: Discussionmentioning
confidence: 78%
“…lauricola show different vessel diameters. The most sensitive cultivars have both larger vessel diameters and hydraulic conductivity than the less susceptible cultivars [ 46 ]. However, when comparing swamp bay, avocado and another closely related species, Persea borbonia , swamp bay is less sensitive to the pathogen despite possessing vessels with large diameters.…”
Section: Discussionmentioning
confidence: 99%
“…Even if in some pathosystems the relationship between xylem structure and susceptibility to vascular pathogens is well documented (such as in elm [ 107 , 180 ] and grapevine [ 103 , 125 ]), for other host plants, this correlation is weakly sustained due to several reasons: the lack of literature on emerging pathogens, the remarkable inter- and intraspecific diversity of plants, the environmental conditions that can modify the structure of xylem vessels [ 181 , 182 ], and the pathogens’ variability. However, it is known that plants evolve their defenses against vascular pathogens [ 183 ], such as the ability to confine microorganisms and their eventual toxic compounds via compartmentalization [ 102 , 125 ]. Among the many features of a xylem vessel, diameter is the main element that can influence tolerance or susceptibility to wilt diseases [ 125 ] also because a low amount of tyloses [ 104 ] (and energy) is required for pathogen compartmentalization in small vessels [ 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even on avocado trees ( Persea americana Mill. ), it was found that the cultivar susceptible to the fungus Raffaelea lauricola (Harr., Fraedrich and Aghayeva) possesses vessels with a larger average diameter than the resistant cultivars , but no significant differences were found in vessel aggregation and density [ 102 ] ( Figure 2 C). The hypothesis is that smaller vessels are quicker compartmentalized by the host with gums and tyloses, and a small number of pits with a lower area can limit the spread between vessels of the pathogen [ 108 ].…”
Section: Wood Anatomy Cavitation and Resistance To Pathogensmentioning
confidence: 99%
See 1 more Smart Citation